2019
DOI: 10.3947/ic.2019.51.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Role of Upper Gastrointestinal Endoscopy in Patients with Human Immunodeficiency Virus Infection in the Era of Combination Antiretroviral Therapy

Abstract: Background Gastrointestinal (GI) diseases are common in patients with human immunodeficiency virus (HIV) infection. There are few reports on the epidemiology and endoscopic findings of gastric cancer in patients with HIV infection in the era of combination antiretroviral therapy (cART). We retrospectively analyzed upper GI endoscopic findings in patients with HIV infection and investigated their role as gastric cancer screening. Materials and Methods We retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Infections with human retroviruses HIV (human immunodeficiency virus) or HTLV (human T-cell lymphotropic virus) increase the risk of developing various tumors, and can also indirectly affect gastric tumorigenesis [ 234 , 235 ]. HIV infection, if left untreated, leads to acquired immunodeficiency syndrome, a disease characterized by immune suppression and loss of immune-mediated control against diverse opportunistic pathogens.…”
Section: Other Carcinogenic Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections with human retroviruses HIV (human immunodeficiency virus) or HTLV (human T-cell lymphotropic virus) increase the risk of developing various tumors, and can also indirectly affect gastric tumorigenesis [ 234 , 235 ]. HIV infection, if left untreated, leads to acquired immunodeficiency syndrome, a disease characterized by immune suppression and loss of immune-mediated control against diverse opportunistic pathogens.…”
Section: Other Carcinogenic Virusesmentioning
confidence: 99%
“…Sixty percent of HIV-infected patients were positive for antibodies to EBV early antigen (EA) compared to 12% of uninfected individuals [ 237 ]. GC precursor lesions, including intestinal metaplasia and atrophic gastritis, were also common in patients infected with HIV [ 234 ]. In contrast to HIV, a large population-based study of HTLV-1-infected subjects found a reduced risk of GC development [ 238 ].…”
Section: Other Carcinogenic Virusesmentioning
confidence: 99%
“…In addition to EBV, various other viruses have been found to contribute to tumorigenic changes in the stomach. These viruses include John Cunningham virus (JCV) ( Murai et al, 2007 ), human cytomegalovirus (HCMV) ( Jin et al, 2014 ; Fattahi et al, 2018 ; Kosari-Monfared et al, 2019 ), hepatitis B (HBV) or C (HCV) viruses ( Song et al, 2019 ; Cui et al, 2020 ; Huang et al, 2020 ), human immunodeficiency virus (HIV) or human T-cell lymphophilic virus (HTLV) (Matsumoto et al, 2018; Kang et al, 2019 ; Schierhout et al, 2020 ), and papillomavirus (HPV) ( Zeng et al, 2016 ; Bozdayi et al, 2019 ).…”
Section: Gastric Microecological Dysbiosis and Gastric Cancermentioning
confidence: 99%
“…The frequency of these complications is influenced by various factors including immune characteristics. Duodenal and gastric ulcers appear to be less frequent in PLWH than in the general population, while gastric cancer has been reported to be 1.8-fold more frequent in PLWH than in the general population in South Korea, a region with a high risk of gastric cancer [3,8].…”
Section: Introductionmentioning
confidence: 99%